The change from UMAT to UCAT for undergraduate medical school applicants: impact on selection outcomes. Issue 2 (30th November 2020) - Griffin, Barbara; Horton, Graeme L; Lampe, Lisa; Shulruf, Boaz; Hu, Wendy
Abstract: Objectives: To assess whether the change from the Undergraduate Medical and Health Sciences Admissions Test (UMAT; 1991–2019) to the University Clinical Aptitude Test (UCAT) for the 2020 New South Wales undergraduate medical degree intake was associated with changes in the impact of sex, socio‐economic status and remoteness of residence, and professional coaching upon selection for interview. Design, setting, participants: Cross‐sectional study of applicants for the three NSW undergraduate medical programs for entry in 2019 (4114 applicants) or 2020 (4270); 703 people applied for both intakes. Applicants selected for interview were surveyed about whether they had received professional coaching for the selection test. Main outcome measures: Scores on the three sections of the UMAT (2019 entry cohort) and the five subtests of the UCAT (2020 entry); total UMAT and UCAT scores. Results: Mean scores for UMAT 1 and 3 and for all four UCAT cognitive subtests were higher for men than women; the differences were statistically significant after adjusting for age, socio‐economic status, and remoteness. The effect size for sex was 0.24 (95% CI, 0.18–0.30) for UMAT total score, 0.38 (95% CI, 0.32–0.44) for UCAT total score. For the 2020 intake, 2303 of 4270 applicants (53.9%) and 476 of 1074 interviewees (44.3%) were women. The effect size for socio‐economic status was 0.47 (95% CI, 0.39–0.54) for UMAT, 0.43 (95% CI, 0.35–0.50) for UCAT total score; the effect size for remoteness was 0.54 (95% CI, 0.45–0.63) for UMAT, 0.48 (95% CI, 0.39–0.58) for UCAT total score. The impact of professional coaching on UCAT performance was not statistically significant among those accepted for interview. Conclusions: Women and people from areas outside major cities or of lower socio‐economic status perform less well on the UCAT than other applicants. Reviewing the test and applicant quotas may be needed to achieve selection equity.